CEO Society : the Corporate Takeover of Everyday Life - Bloom, Peter; Rhodes, Carl (Book Network Int'l Limited trading as NBN International (NBNi) : Zed Books, 2018)
Why have CEOs become the cultural icons of the 21st century?